Passions and social irrationality - Borges, Maria (Studia Kantiana, 2023)
In this paper, I analyze the concept of passions in Kant, trying to answer the question: are passions good for society or are they the source of evil and irrationality? I begin by showing the danger of passions, if compared with affects. In the Anthropology, as well in the Religion, Kant claims that passions are the evil we should fight against. More than inclinations, or affects, the evil principle refers to passions. However, in the Ideia for an Universal history with a cosmopolitan aim, Kant admits that passions are good for society. They are not the cause of their irrationality, but the possibility of the development of the natural predispositions of human being. I claim that we have two distinct answers in Kant, and I try to understand this ambiguity.